2020
DOI: 10.3390/app10186339
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Compaction Load and Procedure on Stress-Deformation Behaviors of a Soil Geosynthetic Composite (SGC) Mass—A Case Study

Abstract: Fill compaction in the construction of Geosynthetic Reinforced Soil (GRS) mass is typically performed by operating a vibratory or roller compactor, which in turns imposed a compaction load in direction perpendicular to the wall face. The compaction process resulted in the development of the so-called compaction-induced stress (CIS), which may subsequently increase the stiffness and strength of the fill material. Compaction process is normally simulated using one of the following compaction procedures—(i) a uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Figure 2 depicts the typical geometry, loading condition, interface elements, and finite element mesh configured in the simulated SGC mass. The sensitivity of mesh sizes was examined, for examples, by Wu and Pham [4] and Gui et al [8]; the numerical results suggested that, to produce sufficiently accurate results, fine mesh without refinement should be chosen when performing simulation on the GRS problem. Thus, a fine mesh without refinement was used to discretize the model.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 2 depicts the typical geometry, loading condition, interface elements, and finite element mesh configured in the simulated SGC mass. The sensitivity of mesh sizes was examined, for examples, by Wu and Pham [4] and Gui et al [8]; the numerical results suggested that, to produce sufficiently accurate results, fine mesh without refinement should be chosen when performing simulation on the GRS problem. Thus, a fine mesh without refinement was used to discretize the model.…”
Section: Methodsmentioning
confidence: 99%
“…These experiments not only showed that the reinforcement spacing plays a more prominent role than the reinforcement strength but also revealed that the behavior of closely spaced reinforced soil can be designated as a nonhomogeneous GRS. Two-dimensional (2D) finite element (FE) analyses have also been performed by References [3][4][5][6][7][8][9] with the aim to appraise the composite behavior of the GRS mass experimented by Pham [3]. In particular, Pham [3] performed a number of finite element analyses and examined the effect of specimen sizes on the overall stress-strain and volumetric change distributions of the SGC mass with the aim to determine a generic dimension for the SGC mass that would produce a sufficiently close load-deformation behavior of a large GRS mass.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The numerical methods have many advantages over laboratory experiments and field measurements, including obtaining more thorough results, examining the effects of various loading conditions, and researching the effects of various variables and parameters, which are challenging or expensive to achieve in laboratory and field tests. To assess the composite behavior of the GRS walls under static loading, two-dimensional (2D) numerical modeling studies have been carried out [26][27][28][36][37][38]44].…”
Section: Introductionmentioning
confidence: 99%